2004
DOI: 10.3748/wjg.v10.i12.1699
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, endoplasmic reticulum stress, and alcoholic liver injury

Abstract: Deficiencies in vitamins or other factors (B6, B12, folic acid, betaine) and genetic disorders for the metabolism of the non-protein amino acid-homocysteine (Hcy) lead to hyperhomocysteinemia (HHcy). HHcy is an integral component of several disorders including cardiovascular disease, neurodegeneration, diabetes and alcoholic liver disease. HHcy unleashes mediators of inflammation such as NFκB, IL-1β, IL-6, and IL-8, increases production of intracellular superoxide anion causing oxidative stress and reducing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(110 citation statements)
references
References 140 publications
2
106
0
2
Order By: Relevance
“…Previously, we reported that homocysteine, a known ER stressor (11), which is elevated in DR (12), up-regulated VEGF expression through an endoplasmic reticulum stress response pathway that was dependent on activating transcription factor 4 (ATF4) (13). ATF4 protein levels increase in response to cellular stresses that cause global protein synthesis to be diminished.…”
Section: From the Department Of Biochemistry And Molecular Biology Umentioning
confidence: 99%
“…Previously, we reported that homocysteine, a known ER stressor (11), which is elevated in DR (12), up-regulated VEGF expression through an endoplasmic reticulum stress response pathway that was dependent on activating transcription factor 4 (ATF4) (13). ATF4 protein levels increase in response to cellular stresses that cause global protein synthesis to be diminished.…”
Section: From the Department Of Biochemistry And Molecular Biology Umentioning
confidence: 99%
“…Within the methionine metabolic cycle, SAM has the properties of lowering homocysteine while increasing the levels of the antioxidant glutathione (GSH), and it also regulates DNA methylation and nucleotide composition (Halsted, 2004). Other studies, including our own, linked hyperhomocysteinemia and elevated S-adenosylhomocysteine (SAH) levels to hepatic endoplasmic reticulum (ER) stress mechanisms (Esfandiari et al, 2005;Ji and Kaplowitz, 2003), whereas hepatic lipid accumulation and hepatocellular apoptosis in ethanol-fed mice were prevented by betaine, a compound that corrects abnormal methionine metabolism by lowering homocysteine and SAH levels (Ji and Kaplowitz, 2004).…”
mentioning
confidence: 99%
“…Hyperhomocysteinemia may increase the myocardial wall dysfunction by excessive production of reactive oxygen species which is made evident by increased lipid peroxidation [22][23][24].…”
Section: Discussionmentioning
confidence: 99%